KAJIAN SIFAT KIMIA TANAH, PERTUMBUHAN DAN PRODUKSI PADI PADA TANAH SULFAT MASAM POTENSIAL AKIBAT PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK SP-36 - Sri Wahyuni Tambunan; Fauzi Fauzi; Marpaung Purba (Universitas Sumatera Utara, 2013)
The objective of this research is to study the effect of empty palm oil bunch compost (EPOBC) andthe application of phosphorus fertilizer of SP-36 on chemical characteristic of acid sulphate soils,rice growth and production (Oryza sativa L.). This study used a randomized block design factorial,with 2 factors: factor 1: compost EPOBC treatment (B) which consist of: B0 = 0 ton ha-1 (0g EPOBC/pot) ; B1 = 10 ton ha-1 (40 g EPOBC/pot); B2 = 20 ton ha-1 (80 g EPOBC/pot);B3 = 30 ton ha-1 (120 g EPOBC/pot) . Factor 2: fertilizer phosphorus (P) which consist of : P0 = 0kg SP-36 ha-1 (0 g SP-36/pot); P1 = ½ dose (1/2 x 135), advice equal with 0,27 g SP-36/pot; P2 = 1,0dose (1 x 135), advice equal with 0,54 g SP-36/pot; P3 = 1 ½ dose (1 1/2 x 135), advice equal with0,81 g SP-36/pot. The results of this research showed that EPOBC treatment significantly affectedsoil pH and Fe2+ reduction, C-organic, seed total and dry weight of rice. While the application ofSP-36 fertilizer non significantly affected P-available and height of plants. Combination betweenEPOBC and fertilizer SP-36 significantly increased seed total and dry weight of rice.Key words: acid sulphate soil, EPOBC, SP-36,rice